Risk Factors for High-Titer Inhibitor Development in Children with Hemophilia A: Results of a Cohort Study. (1st October 2013) - Halimeh, Susan; Bidlingmaier, Christoph; Heller, Christine; Gutsche, Sven; Holzhauer, Susanne; Kenet, Gili; Kurnik, Karin; Manner, Daniela; Iorio, Alfonso; Nowak-Göttl, Ulrike
Abstract : Among the discussed risk factors for high-titre inhibitor (HRI) development in patients with hemophilia A (HA) are high dose FVIII replacement therapy and use of recombinant FVIII concentrates (rFVIII). The aim of this study was to evaluate the aforementioned risk factors for HRI development in children with hemophilia A ≤2%. About 288 ascertained PUPs (Israel and Germany) were followed after initial HA diagnosis over 200 exposure days. Inhibitor-free survival, hazard ratios (HR), and 95% confidence intervals (CIs) were calculated. Adjustment was performed for factor VIII concentrates, median single dose over the first three months of treatment, first FVIII administration before the age of three months, presence of risk HA gene mutations, "intensive treatment moments" and "year of birth" (proxy for different treatment periods). HRI occurred in 71/288 children (24.7%). In multivariate analysis adjusted for "year of birth", underlying risk gene mutations (HR/CI: 2.37/1.40–3.99), FVIII dose, measured per one IU increase per kgbw (HR/CI: 1.05/1.04–1.07), and first FVIII administration before the age of three months showed a significant impact on HR development. The risk of HRI development was similar for recombinant or plasmatic FVIII products. Children at risk should be treated with carefully calculated lower dose regimens, adapted to individual bleeding situations.